Handling Information Security Wisely Utilising the Aggressive Cuckoo Search Algorithm in Lock Systems - Balaji, Adusumalli; Priyadarsini, Ch. Indira; Rao, Eluri Nageswara; Kumar, Gowru Bharath; Nagaraju, Arumalla; Srikanth, Narne; Srinivasarao, Popuri (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Concerns relating to safety and privacy have been brought to light as a result of the growing adoption of Internet of Things (IoT) devices, such as smart home appliances, mobile phones, and smart watches. Security has emerged as an essential component in the development of Internet of Things (IoT) systems in light of the growing number of assaults that originate from both malicious and non-malicious sources. The increasing volume of data that is stored in IoT systems presents a number of unique challenges, one of the most crucial being data security. Hackers may be able to remotely take control of Internet of Things devices if inadequate security measures are in place, which may result in substantial harm. This research suggests utilizing the Aggressive Cuckoo Search Algorithm method (ACS), the SHA-256 method, and the Elliptic Curve Cryptography (ECC) in order to solve these issues while enhancing the safety of internet of things (I smart door lock systems. ACS stands for Aggressive Cuckoo Search, SHA-256 stands for Secure Hash Algorithm, and ECC stands for Elliptic Curve Cryptography. In order to produce the ECC private key, the suggested architecture makes use of ACS, which has the potential to improve the data storage security of IoT systems. In the study, both the encoding and decoding times of the suggested design are analyzed, and it is compared to other encoding methods like (ECC-GA-SHA-256) and (ECC-FA-SHA-256). The findings indicate that the proposed design is capable of producing superior outcomes with 125 iterations for the encoding process and 175 iterations for the decoding process. In addition, the proposed design features encoding and decoding times that are over 16.17 percentage points faster than those of previous encoding methods. Based on these data, it appears that the design that was proposed has the potential to considerably improve the functionality and safety of IoT-based smart door lock systems. The employment of ACS, SHA-256, and ECC can serve as potential solutions to overcome the security concerns connected with IoT-based intelligent locking systems. These are all cryptographic standard algorithms.